Self motivation, compliance, and reasons for attending the La Crosse Exercise and Health Program - Adult Fitness Unit - Kowalski, Thomas (My University, 1989)
This study examined factors such as self-motivation and exercise habits (compliance or noncompliance) as well as participant reasons for attending the La Crosse Exercise and Health Program Adult Fitness Unit. Participants were categorized as compliant (C) or noncompliant (NCOMP), a.m. or p.m., and male or female. Self-Motivation Scores were determined by the Self Motivation Inventory (SMI) and participants were categorized into Low Self Motivators (LSM) , Medium Self Motivators (MSM) or High Self Motivators (HSM). In addition, an Evaluation Questionnaire was developed by the researcher which addressed many of the factors relating to program compliance. The two instruments were administered to 79 Adult Fitness Ss, with a return rate of 77.2 percent. A chi-square test revealed no significant differences between SMI scores and each of the participant groupings. Further, no significant difference was found between exercise habits and each of the groups addressed. The C Ss were more likely to participate in aerobic exercise sessions outside of the program than the NCOMP. More C Ss strongly agreed that their graded exercise test (gxt) was clearly explained to them. A.M. and male Ss joined upon the recommendation of their physician, while p.m. and female Ss joined because of family or spousal influence. A larger percentage of the a.m. Ss believed the exercise sessions did not interfere with daily activities and that the facilities were easily accessible to home and/or work. A larger percentage of the female Ss believed the exercise facilities were clean and pleasant compared to the male Ss.
Keywords: Heart -- Diseases -- Patients -- Wisconsin -- La Crosse -- Attitudes; La Crosse (Wis.) -- Public opinion.; La Crosse Exercise Program (University of Wisconsin--La Crosse) -- Adult Fitness Unit -- Public opinion.